Taking into account the indicators of physical health and physical readiness of students in the development of the program of sectional classes in Thai boxing - Alexander Chuyko (Kharkiv State Academy of Physical Culture, 2018)
Purpose: assess the level of physical health and physical preparedness of students 17-19 years to develop a program of sectional classes in Thai boxing. Material & Methods: analysis of scientific and methodological literature, pedagogical observation, pedagogical experiment, anthropometric, physiological methods of research, pedagogical testing of physical preparedness, express assessment of physical health by the method of G. L. Apanasenko, methods of mathematical statistics. The study involved 77 young students aged 17-19 years. Results: obtained data during the experiment showed a predominantly low and below average level of physical health, as well as the lag of some physical qualities from age standards. Conclusion: the evaluation of physical health and physical preparedness indicators of 17-19 years old boys testifies to the need to develop and implement training programs aimed at increasing the level of physical health and the development of physical qualities.